Deletion at chromosome band 20p12.1 in colorectal cancer revealed by high resolution array comparative genomic hybridization. - Davison, E; Tarpey, P; Fiegler, H; Tomlinson, I; Carter, N (2005)
Array comparative genomic hybridization (Array CGH) with tiling path resolution for a approximately 4.61 Mb region of chromosome band 20p12.1 has been used to investigate copy number loss in 48 colorectal cancer cell lines and 37 primary colorectal cancers. A recurrent deletion was detected in 55% of cell lines and 23% of primary cancers and the consensus minimum region of loss was identified as a approximately 190 kb section from 14.85 Mb to 15.04 Mb of chromosome 20. Two noncoding RNA genes located in the region, BA318C17.1 and DJ974N19.1, were investigated by mutation analysis and real-time PCR in colorectal cancer cell lines. Sequence changes in BA318C17.1 and reduced expression of both genes was detected, suggesting that the abrogation of these genes may play a role in colorectal tumorigenesis.